Dopaminergic and Cholinergic Modulation of Striatal Tyrosine Hydroxylase Interneurons - Ibáñez-Sandoval, Osvaldo (Neuropharmacology, 2015)
The recent electrophysiological characterization of TH-expressing GABAergic interneurons (THINs) in the neostriatum revealed an unexpected degree of diversity of interneurons in this brain area (Ibáñez-Sandoval et al., 2010, Unal et al., 2011, 2013). Despite being relatively few in number, THINs may play a significant role in transmitting and distributing extra- and intrastriatal neuromodulatory signals in the striatal circuitry. Here we investigated the dopaminergic and cholinergic regulation of THINs in vitro. We found that the dominant effect of dopamine was a dramatic enhancement of the ability of THINs to generate long-lasting depolarizing plateau potentials (PPs). Interestingly, the same effect could also be elicited by amphetamine-induced release of endogenous dopamine suggesting that THINs may exhibit similar responses to changes in extracellular dopamine concentration in vivo. The enhancement of PPs in THINs is perhaps the most pronounced effect of dopamine on the intrinsic excitability of neostriatal neurons described to date. Further, we demonstrate that all subtypes of THINSs tested also express nicotinic cholinergic receptors. All THIS responded, albeit differentially, with depolarization, PPs and spiking to brief application of nicotinic agonists. Powerful modulation of the nonlinear integrative properties of THINs by dopamine and the direct depolarization of these neurons by acetylcholine may play important roles in mediating the effects of these neuromodulators in the neostriatum with potentially important implications for understanding the mechanisms of neuropsychiatric disorders affecting the basal ganglia.